1975
DOI: 10.1159/000102647
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stereotactic Lesions of the Dentate Nucleus of the Cerebellum in Man

Abstract: In a series of 50 patients, 94 stereotactic lesions involving different parts of the dentate nuclei of the cerebellum were performed. 47 patients exhibited various dyskinetic syndromes; among these, 7 were also affected by epilepsy. In 3 patients epileptic disorders were exclusively present. Favourable results were obtained in dystonic and dystonic-athetoid infantile syndromes, more than in spastic syndromes. Some interesting effects on the epilepsy and ocular motility are also noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…The cerebellum is critical in the fluency of speech. Fraioli and Guidetti performed stereotaxic ablation on the dentate nucleus and its outflow tract, the superior cerebellar peduncle, which resulted in reversible mutism [13]. This may explain the development of mutism in patients with posterior fossa lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellum is critical in the fluency of speech. Fraioli and Guidetti performed stereotaxic ablation on the dentate nucleus and its outflow tract, the superior cerebellar peduncle, which resulted in reversible mutism [13]. This may explain the development of mutism in patients with posterior fossa lesions.…”
Section: Discussionmentioning
confidence: 99%
“…45,96 In 1949 Brown included dysarthria when describing cerebellar syndrome, 69 while in 1972 Stein was the first to "incidentally" report CM. 31 In 1975 Fraioli and Guidetti 29 …”
Section: Historical Overviewmentioning
confidence: 99%
“…The dentate nucleus was the first region that was hypothesized to be involved. Fraioli and Guidetti 29 reported on 2 patients with complete absence of speech after bilateral stereotactic lesioning of the dentate nuclei. Later on many authors proposed that bilateral damage of the dentate nuclei is a critical factor for CM.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Early studies demonstrated that stimulations or lesions of specific thalamic nuclei could alleviate dystonia in some patients [35][36][37][38]. In a few patients, surgical lesion of the dentate output nucleus of the cerebellum was also shown to alleviate dystonia [16][17][18][39][40][41][42] suggesting the involvement of this structure in the generation of some dystonia. However, a major caveat of these early surgical interventions is that the results were simply reported as case studies without the scientific rigor to allow unbiased evaluation of their efficacy.…”
Section: Clues From Surgical Interventionsmentioning
confidence: 99%
“…Another region implicated in some secondary dystonias that has received increasing attention in recent years is the cerebellum [13,14]. Historically there are numerous case reports linking cerebellar insult with dystonic symptoms [15][16][17][18] and recent studies corroborate association of dystonic symptoms with cerebellar injury [19][20][21][22].…”
mentioning
confidence: 99%